A CASE STUDY ON AWARENESS OF THE IMPORTANCE OF ZAKAT FITRAH AMONG STAFF IN JERANTUT DISTRICT ISLAMIC RELIGIOUS OFFICE - Johar, Muhammad Asri Fahmi; Musa, Muhammad Fadhli; Nik Mohd Zainordin, Nik Mohamad Shamim (Journal of Islamic, Social, Economics and Development, 2024)
Zakat fitrah is very important in our lives. Either the person who receives zakat or the person who issues zakat. Awareness of the importance of zakat to our society is low. The reason why the payment of zakat is important is because the purpose of zakat itself is to help the poor and needy. With the help of Zakat Fitrah, at least they can change their lives as with the help of zakat earned, they can cover the increasingly high cost of living nowadays. This has been supported through this study from the factors that affect the insensitivity of zakat payment. As a result, the main purpose of this study is to study and find factors that encourage all Muslims to be less sensitive to the importance of zakat fitrah. This study was conducted on the staff of the Jerantut District Islamic Religious Office (PAID). This study is based on data from a questionnaire survey that was distributed to 40 officers and staff and only 34 people were selected as a sample for this study. After analyzing the data, the research findings show that the officers and staff have a good understanding of the science of zakat fitrah, but their level of awareness about the importance of zakat fitrah should be further improved. As a result of this study, zakat institutions and society need to improve in all aspects to create more awareness of the importance of zakat fitrah. Suggested solutions are also written in this study to increase the level of awareness to be more sensitive to the importance of zakat fitrah.